Preparation of PCU/PPy composites with self-healing and UV shielding properties - Xiong, Zhengrong; Zhang, Hang; Zhou, Yan; Yang, Yuming (Frontiers in Materials, 2022)
Polycarbonate-based polyurethanes (PCU) are frequently used in airship envelope materials because of its outstanding mechanical performances and aging resistance. However, the surface of PCU is likely damaged during processing and operating and the emerged minuscule cracks will lead to deterioration of perfomances for airship’s envelope materials. Herein, self-healing PCU/polypyrrole nanoparticles (PPy) composites were prepared by solution blending and quick healing of specific area for PCU was realized due to the high photo-thermal conversion merit of PPy. The results show that, the mechanical properties of PCU/PPy composites can be restored to more than 80% and the gas barrier properties can also be basically repaired when irradiating the destroyed surface using near-infrared light for only 60s. In addition, the ultraviolet visible(UV-vis) shielding performance of the PCU/PPy composites was enhanced significantly and the UV-vis transmittance was less than 14% and 2% with 0.25wt% and 0.5wt% PPy, respectively. Meanwhile the tensile strength are improved from 17.9MPa to 21.7MPa with the corresponding elongation at break from 647% to 829% when adding 0.25wt% PPy. Besides, the thermal decomposition temperature at 5wt% loss increased from 277.8ºC to 300.7ºC and 304.88ºC with 0.25 wt% and 0.5 wt% PPy, respectively. The prepared composites show promising application in aerospace domain.